A turizmus helyzetének változása az Alföldön és a jelenség térbeli terjedése Magyarországon - Csordás, László (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Between 1990-2007 the number of commercial and private accomodation rooms, and the number of the catering establishments increased most dynamically (more than 30%) on the Great Hungarian Plain. The inland tourism developed dynamically too: the proportion of inland guests’ increased from 45 to 76%, and the guest nights from 47 to 71%. The 6 plain counties so in the future primarily the scenes of the domestic tourism. The number of foreign guests decreased 50%, the foreign guest nights with 33%. The 30% of the South-Plain and 23% of the North-Plain settlements engaged in the tourist traffic registered on the commercial accomodation rooms. The forming of the accomodations so contributed to the tourists’ evener spatial distribution, the solution of the congestion of centres, for the background settlements of the centres until now and to involving the areas handled as a blind spot tourismwise earlier in the tourism.